The effects of interest rate increases on consumers' inflation expectations: The roles of informedness and compliance - Edward S. Knotek; James Mitchell; Mathieu Pedemonte; Taylor Shiroff (Inter-American Development Bank (IDB), 2024)
We study how monetary policy communications associated with increasing the federal funds rate causally affect consumers inflation expectations in real time. In a large-scale, multi-wave randomized controlled trial (RCT), we find weak evidence that communicating these policy changes lowers consumers medium-term inflation expectations on average. However, information differs systematically across demographic groups, in terms of ex ante informedness about monetary policy and ex post compliance with the information treatment. Monetary policy communications have a much stronger effect on the subset of consumers who had not previously heard news about monetary policy and who take sufficient time to read the treatment. Our findings show that, in an inflationary environment, these consumers expect that raising interest rates will lower inflation. More generally, our results emphasize the importance of measuring both respondents information sets and their compliance with treatment when using RCTs in empirical macroeconomics to better understand the real-world implications of monetary policy communications.
Keywords: E31; E52; E58; 330; Expectations formation; Policy communication; Monetary policy; Inflation; Surveys